2017
DOI: 10.1175/jas-d-17-0067.1
|View full text |Cite
|
Sign up to set email alerts
|

The Semiannual Oscillation of the Tropical Zonal Wind in the Middle Atmosphere Derived from Satellite Geopotential Height Retrievals

Abstract: The dominant mode of seasonal variability in the global tropical upper-stratosphere and mesosphere zonal wind is the semiannual oscillation (SAO). However, it is notoriously difficult to measure winds at these heights from satellite or ground-based remote sensing. Here, the balance wind relationship is used to derive monthly and zonally averaged zonal winds in the tropics from satellite retrievals of geopotential height. Data from the Aura Microwave Limb Sounder (MLS) cover about 12.5 yr, and those from the Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
110
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(135 citation statements)
references
References 30 publications
12
110
1
Order By: Relevance
“…1c) instead we identify SAO-related variations around 5 × 10 −3 and 10 −4 hPa. Similar structures are found in satellite data (Smith 2012;Smith et al 2017) and in other model simulations (PO10). The agreement of these mesospheric SAO structures with the present simulation is only qualitative.…”
Section: Resultssupporting
confidence: 87%
“…1c) instead we identify SAO-related variations around 5 × 10 −3 and 10 −4 hPa. Similar structures are found in satellite data (Smith 2012;Smith et al 2017) and in other model simulations (PO10). The agreement of these mesospheric SAO structures with the present simulation is only qualitative.…”
Section: Resultssupporting
confidence: 87%
“…The migrating semidiurnal tide (westward k = 2) is not properly sampled, but its amplitude is relatively small in the range of altitude and latitude considered here (Wu et al, 2006). However, we find that above 80 km, where the amplitude of the migrating diurnal tide grows rapidly, some aliasing of the time mean is present, which originates ultimately from the sampling of tidal variability across the slightly shifted space-time coordinates of the observations in successive yaw maneuvers (see Smith et al, 2017). Nonetheless, here we use temperature series over the pressure range 80 to 5 × 10 −4 hPa (~17 to 95-km geometric altitude), since the time mean is irrelevant for the determination of the trend.…”
Section: Saber Observationsmentioning
confidence: 80%
“…We use SABER version 2 (v.2) data for temperature, which is available from http://saber.gats-inc.com/data.php. Smith et al (2017) showed that SABER data can be binned as a function of altitude and pressure to construct continuous time series suitable for processing using Salby's (1982aSalby's ( , 1982b Fast Fourier Synoptic Mapping (FFSM) method. FFSM operates on asynoptic observations to produce synoptic spectra in zonal wave number and frequency, whence behavior in the space-time domain can be reconstructed.…”
Section: Saber Observationsmentioning
confidence: 99%
“…Simulations used here are based on the guidelines from the International Global Atmospheric Chemistry -Stratosphere-troposphere Processes And their role in Climate (IGAC/SPARC) Chemistry-Climate Model Initiative (Morgenstern et al, 2017). Improvements in CESM1 WACCM for CCMI include a modification to the orographic gravity wave forcing, which reduced the cold bias in Antarctic polar temperatures (Garcia et al, 2017;Calvo et al, 2017), and updates to the stratospheric heterogeneous chemistry, which improved the representation of polar ozone depletion (Wegner et al, 2013;Solomon et al, 2015). In this work, there are two CCMI scenarios, spanning the 1990-2014 period.…”
Section: Gozcardsmentioning
confidence: 99%
“…S4 for the relevant time series). Uncertainties regarding lower-stratospheric heterogeneous chemistry modeling for SD-WACCM at high latitudes in the polar winter and spring have been discussed by Solomon et al (2015) for one specific year (2011), including most of the features shown in Fig. 7.…”
Section: Average Abundancesmentioning
confidence: 99%